Persepsi Siswa Terhadap Penggunaan Whatsapp Pada Pembelajaran Pendidikan Agama Islam (PAI) Daring di SMP Negeri 03 Tangerang Selatan - Firda Afifa Tunnissa; Hasanah (STIT Muslim Asia Afrika, 2021)
This research departs from the problem of the impact of the Covid-19 Pandemic on the education aspect, which requires teaching and learning activities to be carried out from home, namely through online learning. In online learning, internet-based learning media is needed. The change in learning conditions due to the Covid-19 pandemic is the background of the author's interest in discussing online learning, especially in PAI subjects that use WhatsApp as a learning medium based on student perceptions at SMP Negeri 03 South Tangerang. This study uses a qualitative approach with a qualitative descriptive type of research. Primary data were obtained through field observations and interviews with 1 teacher of Islamic religious education and 5 students of SMP Negeri 03 Tangerang Selatan. Secondary data sources are obtained from books, journals, and other scientific writings that support the research. The findings from this study are that according to some students learning to use WhatsApp contains positive values, online learning using WhatsApp is easy, many features can be used. then some students stated that learning through Whatsapp was less effective due to the lack of interaction between teachers and students, the focus of students on the material taught by the teacher was still lacking, and the material taught by the teacher was sometimes difficult for students to understandAs for the obstacles that occur when online learning through WhatsApp, not all students have smartphones, signal problems, Smartphone memory is full, the application used is only WhatsApp, students are less enthusiastic when learning , and students find it difficult to understand the material taught by the teacher.